Islamic Social Finance: Bridging Maqasid Al-Shariah and Sustainability - Junaidah Abu Seman; Nurul Syafiqah Mohamad Nasir; Fauzias Mat Nor; Syahidawati Hj. Shahwan; Nurul Aini Muhamed; Ainulashikin Marzuki; Nur Ainna Ramli (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA